Utilizing Remote Sensing Data to Evaluate the Urban Heat Island: A Case Study of Quetta City, Balochistan - Zakaria Shah; Romana Ambreen; Niamat Ullah; Shafi Ullah; Syed Wajid Hanif Bukhari (Indus Journal of Social Sciences, 2025)
The urban heat island (UHI) effect presents a significant environmental challenge in rapid urbanization. Its mitigating impacts on public health, power consumption, and urban livability require a brief understanding of energy dynamics. MODIS satellite data, has detailed spatial and temporal coverage that serves as an essential tool in analyzing temperature trends, changes in land cover, and other related variables. Therefore, this study leverages MODIS data to analyze the impact of UHI, identifying significant changes in temperature distribution patterns over time. Our results inferred expansion in the high-temperature zone, shrinking in the central temperature zone, and comparatively stable in the low-temperature zone. These trends align with the trajectory of global warming and emphasize a wide-ranged impact on the ecosystem, weather patterns, and human activities. These findings trend a pronounced peak in global warming during the months observed for rainfall, underscoring a clear connection to climate change. However, the analysis highlights the limitations of short-term datasets in capturing long-term UHI trends and calls for more comprehensive temporal data to visualize geographic complexity. urbanization and climate change in the region It provide the basis for creating sustainable urban planning strategies and important step towards achieving climate-friendly urban ecosystems that can mitigate the cascading effects of global warming.